Pemuda Sigap dan Tanggap Covid-19 serta Pembentukan Masyarakat yang Berjiwa Spiritual di masa Pandemi - Irna Tri Yuniahastuti; Ina Sunaryantiningsih (Universitas Mathla'ul Anwar Banten, 2021)
YOUTHS ARE ALERT AND RESPOND TO COVID-19 AND THE ESTABLISH OF A SPIRITUAL COMMUNITY DURING THE PANDEMIC. The corona virus has become a pandemic that has hit all the world, including Indonesia. Along with the increase in the number of infected victims and the death toll on a national scale due to significant exposure to the virus, everyone becomes anxious and worried, including the residents of the village of Kartoharjo, East Java. Several attempts were made by the community and village officials to prevent transmission of the corona virus. Apart from physical effort, spiritual (inner) work is also carried out. Some of the activities carried out to support these efforts include, a) spraying disinfectants on roads, public places and people's homes, b) distributing basic necessities to the poor and affected, c) holding mutual cooperation markets, d) limiting social activities in outside the home, and e) perform